Spreading drops of insecticide syrup with different doses of adjuvants on cassava leaves - Salvalaggio, Adriana Cologni; Costa, Neumárcio Vilanova da; Moratelli, Gustavo; Exteckoetter, Vanessa; Podkowa, Camila Inês; Cazzo, Victor Natan (Scientia Agraria Paranaensis, 2017)
Objetivou-se avaliar a eficiência do espalhamento de gotas em folhas de mandioca de soluções com inseticidas biológicos e adjuvantes em diferentes It was aimed to evaluate the efficiency of spreading drops in cassava leaves of solutions with biological insecticides and adjuvants in different concentrations. The experimental design was completely randomized in a factorial 2 x 3 x 5, with four replications. The treatments consisted in the preparation of solutions of two biological insecticides Bacillus thuringiensis (500 g ha-1, Dipel WP® - 32.0 g kg-1) and Baculovirus (0.41 g ha-1), with addition of three adjuvants (Mineral oil - Nimbus®, vegetable oil - Aureo® and glycerine - Hygrogem®, soybean biodiesel byproduct) in five concentrations (0.0%; 0.2%; 0.4%; 0.6% and 0.8% v v-1), on cassava leaves of variety ‘IAC 90’. The spreading of the drops (13 μL) of the solutions was evaluated in adaxial and abaxial faces. There was triple interaction among factors insecticides, adjuvants and concentration of adjuvants. It was found that the B. thuringiensis + mineral oil (0.5% v v-1) and B. thuringiensis + vegetable oil (0.3% v v-1) provided the largest areas of spreading of droplets on the adaxial and abaxial faces, respectively. The Baculorivus + vegetable oil (0.6% e 0.8% v v-1) provided higher spreading of drops on the adaxial and abaxial faces, respectivelyl. Glycerin in concentrations evaluated, not shown to be effective both in reducing the surface tension of the solutions, as in spreading drops. The efficiency of spreading drops on cassava leaves was dependent on the biological insecticide used and the adjuvant type and concentration used in the preparation of the spray solution.